Evolution of Brain Volume Loss Rates in Early Stages of Multiple Sclerosis - Uher, Tomas; Krasensky, Jan; Malpas, Charles; Bergsland, Niels; Dwyer, Michael G; Kubala Havrdova, Eva; Vaneckova, Manuela; Horakova, Dana; Zivadinov, Robert; Kalincik, Tomas (Neurology® neuroimmunology & neuroinflammation, 2021)
OBJECTIVE: To describe the dynamics of brain volume loss (BVL) at different stages of relapsing-remitting multiple sclerosis (RRMS), to describe the association between BVL and clinical measures, and to investigate an effect of treatment escalation on the rate of BVL. METHODS: Together, 1903 patients predominantly with RRMS from the Avonex-Steroids-Azathioprine cohort (N = 166), the study of early IFN-β1a treatment cohort (N = 180), and the quantitative MRI cohort (N = 1,557) with ≥2 MRI scans and ≥1-year of follow-up were included. Brain MRI scans (N = 7,203) were performed using a single 1.5-T machine. Relationships between age or disease duration and global and tissue-specific BVL rates were analyzed using mixed models. RESULTS: Age was not associated with the rate of BVL (β = -0.003; Cohen f2 = 0.0005; adjusted p = 0.39). Although disease duration was associated with the rate of BVL, its effect on the BVL rate was minimal (β = -0.012; Cohen f2 = 0.004; adjusted p = 4 × 10-5). Analysis of association between tissue-specific brain volume changes and age (β = -0.019 to -0.011; adjusted p = 0.028-1.00) or disease duration (β = -0.028 to -0.008; adjusted p = 0.16-0.96) confirmed these results. Although increase in the relapse rate (β = 0.10; adjusted p = 9 × 10-9), Expanded Disability Status Scale (EDSS; β = 0.17; adjusted p = 8 × 10-5), and EDSS change (β = 0.15; adjusted p = 2 × 10-5) were associated with accelerated rate of BVL, their effect on the rate of BVL was minimal (all Cohen f2 ≤ 0.007). In 94 patients who escalated therapy, the rate of BVL decreased following treatment escalation by 0.29% (β = -0.29; Cohen f2 = 0.133; p = 5.5 × 10-8). CONCLUSIONS: The rate of BVL is relatively stable throughout the course of RRMS. The accelerated BVL is weakly associated with concurrent higher disease activity, and timely escalation to high-efficacy immunotherapy helps decrease the rate of BVL.
Keywords: dospělí; Magnetic Resonance Imaging; Female; Adult; ženské pohlaví; longitudinální studie; lidé; Multiple Sclerosis; magnetická rezonanční tomografie; roztroušená skleróza; mozek; kohortové studie; atrofie; Cohort Studies; prospektivní studie; Male; progrese nemoci; Atrophy; Brain; Prospective Studies; Disease Progression; lidé středního věku; mužské pohlaví; Middle Aged; Longitudinal Studies; Humans